Animal models of cough - Plevkova, Jana; Brozmanova, Mariana; Matloobi, Alireza; Poliacek, Ivan; Honetschlager, Jan; Buday, Tomas (Respiratory physiology & neurobiology, 2021)
Cough is a vital airway reflex that keeps the respiratory tract wisely protected. It is also a sign of many diseases of the respiratory system and it may become a disease in its own right. Even though the efficacy of antitussive compounds is extensively studied in animal models with promising results, the treatment of pathological cough in humans is insufficient at the moment. The limited translational potential of animal models used to study cough causes, mechanisms and possible therapeutic targets stems from multiple sources. First of all, cough induced in the laboratory by mechanical or chemical stimuli is far from natural cough present in human disease. The main objective of this review is to provide a comprehensive summary of animal models currently used in cough research and to address their advantages and disadvantages. We also want to encourage cough researchers to call for precision is research by addressing the sex bias which has existed in basic cough research for decades and discuss the role of specific pathogen-free (SPF) animals.
Keywords: Reflex; Animal welfare; Translation; Animals; kašel; Animal models; Disease Models, Animal; zvířata; Cough; modely nemocí na zvířatech